Effect of maleic anhydride compatibilizer addition on mechanical properties of polylactic acid (PLA)/cellulose acetate (CA) composites film - Abdul Kholiq; Ika Jumantika; Achmad Syarafuddin As-syirazi; Rahmayetty Rahmayetty (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Environmental problems caused by the use of undegradable conventional plastics are still the major issue. According to the Badan Pusat Statistik (BPS) in 2021, plastic waste in Indonesia accumulated as much as 66 million tons per year and is expected to raise gradually. PLA and CA, derived from renewable resources, are biodegradable, thermoplastic, resistant to pressure, and are often used as raw materials for the manufacture of composite plastics. PLA is hydrophobic and CA is hydrophilic, so a compatibilizer is needed as a substance that can improve the mechanical properties, compatibility, and homogeneity of the resulting composite film. This research aims to obtain the ratio of PLA/CA and the concentration of maleic anhydride (MA) compatibilizer to produce PLA/CA composites film with good mechanical strength and according to packaging material standards. The method in this research is solvent casting by synthesizing composite films through sample preparation, modification of CA with MA, grafting of PLA/CA and MA, synthesis of composite films of PLA/CA and MA, as well as several characteristic tests. The results showed that the obtained films were identified as having PLA, CA, and MA, had a relatively smooth surface and were degraded at a temperature treatment of 543oC. The best film was obtained from mass variations of PLA/CA and MA (6:4:1.5 gram) with a tensile strength of 7.38 MPa, and elongation at break reached 18.11% and met the packaging standard values by Japanese Industrial Standard (JIS).